Streets of Cairo or The Poor Little Country Maid, and My Coney Island Girl - James Thornton::::::::: (Frank Harding's Music House)
Song-March, 6 p. At head of title: Bonnie Thorntons latest hit. My Coney Island Girl dedicated to Ben Harris.